2015
DOI: 10.1038/nphoton.2015.128
|View full text |Cite
|
Sign up to set email alerts
|

Status and prospects for ternary organic photovoltaics

Abstract: DTffBT sub-cell J sc = 7.86; V oc = 0.89 DTPyT sub-cell J sc = 6.99; V oc = 0.83 PBHJ cell J sc = 13.5; V oc = 0.87 Figure 4 | J-V curves of representative ternary PSCs. a, A P3HT:PCBM:SiPc system with (solid lines) and without dye (broken lines) before (thin lines) and after annealing (thick lines). Reproduced from ref. 36, ACS. b, A DTffBT:DTPyT:PCBM system. Reproduced from ref. 45, ACS. c, A PTB7:PID2:PCBM system. Reproduced from ref. 33, NPG. d, A α-6T:SubPc:SubNc system. Reproduced from ref. 73, NPG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
416
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(426 citation statements)
references
References 95 publications
10
416
0
Order By: Relevance
“…3,4,[19][20][21][22][23]24 However, simultaneous increase in the Voc, Jsc and FF is a challenge in the ternary approach because of the trade-off between photocurrent and voltage. 23,25,26 Reports show ternary blends using fullerene acceptors, where the Voc is increased using a second acceptor (A2) with a higher electron affinity (EA) than A1; 23,27-29 however, very few examples of two-acceptor ternary blend devices could surpass the overall efficiency of their respective binary blends. 24,30,31 Therefore, the majority of studies on ternary solar cells have focused on multi-polymer donor:acceptor blends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,[19][20][21][22][23]24 However, simultaneous increase in the Voc, Jsc and FF is a challenge in the ternary approach because of the trade-off between photocurrent and voltage. 23,25,26 Reports show ternary blends using fullerene acceptors, where the Voc is increased using a second acceptor (A2) with a higher electron affinity (EA) than A1; 23,27-29 however, very few examples of two-acceptor ternary blend devices could surpass the overall efficiency of their respective binary blends. 24,30,31 Therefore, the majority of studies on ternary solar cells have focused on multi-polymer donor:acceptor blends.…”
Section: Introductionmentioning
confidence: 99%
“…24,30,31 Therefore, the majority of studies on ternary solar cells have focused on multi-polymer donor:acceptor blends. 19,23,[27][28][29] However, the mixing of two polymers is more complicated due to both a lack of entropic driving force for mixing, and the potential for strong intermolecular attractions between polymer chains. 32 Therefore, a ternary approach, wherein small molecule acceptors are mixed in a donor:multi-acceptor blend (D:A1:A2, where D is donor polymer, A1 is the primary acceptor and A2 is a second acceptor), has the potential to offer morphological advantages.…”
mentioning
confidence: 99%
“…Up to now, several excellent reviews have summarized the progress in ternary solar cells based on their unique insights [8,[15][16][17][18][19][20]. So in this article we present a review mainly focused on the newly reported work concerning about ternary blend PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[60][61][62][63] Phenyl-C 61 -butyric acid methyl ester (PC 61 BM; an organic electron-acceptor) 64 is soluble in organic solvents where poly(3-hexylthiophene) (P3HT; an organic electron-donor) is blended over a range of concentrations to prepare thin films with a bulk heterojunction structure. [65][66][67][68][69][70] An OPV based on phenyl-C 71 -butyric acid methyl ester (PC 671 BM) with an n-type conjugated polymer, poly (4,8-…”
mentioning
confidence: 99%